1313Is private rental instability bad for mental health?. (2nd September 2021) - Li, Ang; Bentley, Rebecca
Abstract: Background: People in the private rental sector move more than people in other tenures. Yet we know little about the consequences for health of this instability. We are the first to use a nationally representative longitudinal survey of Australians (2000-2018) to causally examine mental health effects of residential instability for a low-income working-aged cohort of private renters. Methods: Mental health was measured using the SF-36 (MH) and Kessler Psychological Distress scale (K10). We examined effects of 1) cumulative time spent in private rental compared with other sectors (homeowner or social housing), 2) total numbers of transitions, and 3) average numbers of transitions within 5 years, using marginal structural models to account for complex confounding of tenure, socio-economic position, and mental health over time. Results: The mental health of private renters was similar to homeowners at initial occupancy but became worse after one to five years. The more moves private renters made, the worse their mental health, with people who had >five moves in total reporting a -3.77-point (95%CI -6.79; -0.75) difference on MH and -3.84-point difference (95%CI -7.61; -0.07) on K10 (rescaled). If numbers of moves were small, the mental health of private tenants was better than social tenants. When moves were frequent, however, their mental health scores became similar. Conclusions: Residential instability negatively affects mental health. Frequent moves in private rental worsen tenants' mental health compared to owners. Key messages: Reducing housing instability in lower-income households in private rental with greater protection from forced moves will increase resident's wellbeing.